IRB as Poetry. (February 2019) - Lahman, Maria K. E.; Teman, Eric D.; Richard, Veronica M.
In this series of poems, the authors reflexively explore experiences with the institutional review board (IRB) through the use of various poetic forms, including autoethnographic, literature review, artifact, blackout, typewriter, concrete, cutout, photographic, and collage. Areas of the authors' individual research lines are with children, adolescents, and lesbian, gay, bisexual, transgender, queer, questioning, and ally (LGBTQQA+) participants, which are groups federally designated as vulnerable in research. Author experiences with these groups are reflected in the poetry and the perspectives of being reviewed by, reviewers of, and chairs of IRB.